Health Education of Parents About Baby Massage for Stunting Toddler in The Working Area of The Sumbergempol Puskesmas 2024 - Oktaviana, Friska; Widyawati, Evita; Handayani (STIKes Patria Husada Blitar, 2024)
The decline in stunting rates in Indonesia is very slow. Stunting is a condition of failure to thrive in toddlers under 5 years of age which can have a long-term impact on the quality and productivity of the nation's next generation of children. In this era of development, many parents still believe in shamans and lack knowledge about the many benefits of baby massage which can help optimize children's growth and development to prevent stunting. This community service aims to provide health education to parents about baby massage to reduce stunting rates. The results and discussion of this community service were positive responses from 30 parents who had taken part in the activity of providing health education about the benefits of baby massage on children's growth and development. Providing intervention in the form of baby massage can stimulate growth hormones in children so that mothers or parents have the knowledge and motivation to carry out baby massages regularly. The conclusion from this community service is that there is a significant influence of health education about baby massage on mothers' attitudes towards being able to do baby massage as an effort to prevent stunting.